Estudos bioquímicos e estruturais das enzimas celobiohidrolase e endoxilanase do fungo Humicola grisea var. thermoidea - Malaspina, Lorraine Andrade (2014)
Obtaining 3-dimensional structure of an enzyme can be used as an initial step in projects of genetic engineering and enzymatic engineering when aiming for optimization of catalytic activity and/or production of target enzymes on an industrial scale. Currently, crystallography is the most widely used method for the determination of three-dimensional structures of macromolecules. The plant biomass in the form of cellulose, hemicellulose and lignin, have great potential for biotechnological applications. With the growing demand for renewable energy sources, its been proposed it's use to obtain energy, called biofuels. For such purpose, the main approach is the search of the degradation of biomass via enzymatic hydrolysis. In this context, the study of microorganisms capable of carrying out the degradation of biomass and the study of the enzymes involved in this process play a key role. Particularly, the thermophilic fungus Humicola grisea var. thermoidea presents signi cant production of active lignocellulolytic enzymes at high temperature and has been considered a strong candidate for industrial applications. However, the scienti c literature still lacks of structural information on fungal enzymes involved in the hydrolysis of lignocellulose. In previous work, the cellulolytic enzyme cellobiohydrolase (CBH1.2) from Humicola grisea has been identi ed and cloned into Pichia pastoris as well as one of the endoxylanases (HXYN2) from this same organism. In this master's project, the enzymes CBH1.2 and HXYN2 were expressed using heterologous expression system obtaining satisfactory yield for in vitro assays. Puri - cation protocols were established via precipitation by ammonium sulfate and initial experiments of enzyme activity were performed via the reducing sugars method for both enzymes. XX Crystallization conditions were found for the enzyme CBH1.2r, where small needleshaped crystals were obtained in crystallization trials. In addition to this, the cloning of the enzyme CBH1.2 from Humicola grisea with the pHIL-D2 expression vector (for extracellular expression) was performed. This vector was used to transform GS115 and SMD1168 strains of the yeast P. pastoris both with the genotype his4-. Transformants that were able to secrete active protein were detected in both strains.